Stability Analysis On Models Of Spreading H1N1 And H5N1 Virus In Two Locations - Silviana Maya P; Hariyanto Hariyanto; Mahmud Yunus ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2016)
The dynamics of population mobility are occurring in a population. This phenomena can expand the area of the spread of a virus. Allowing the occurrence of a pandemic of a coalition between the H5N1-p virus and H5N1. In this paper, we analyze the stability of the model of the spread of H1N1 and H5N1-p. Based on the basic reproduction number R0, which is then simulated using the Matlab software, we conclude that when R0 < 1 the system is stable, whereas when R0 > 1 the system is unstable.